Hubungan Efek Samping Obat Dengan Length Of Stay (LOS) Pasien Jantung Koroner Di Rumah Sakit “X” - Inaratul Rizkhy Hanifah; Asa Puspagiri Setiyasih; Lucia Vita Inandha Dewi (Fakultas Farmasi Universitas Setia Budi, 2022)
Coronary heart disease (CHD) is caused by the narrowing and blockage of blood vessels that carry blood to the heart. CHD is listed as the highest deadly disease by WHO. CHD treatment is carried out long-term and uses a combination of several drugs, so there is a risk of drug side effects. Length of stay (LOS) is one indicator of successful therapy for CHD patients. However, no correlation studies of LOS with the incidence of drug side effects in CHD patients. Therefore, the purpose of the study was to analyze the potential side effects that occur in CHD therapy and to find the relationship with LOS in the